Uses of FloSeal© in obstetric hemorrhage: Case series and literature review - Jacqueline Pui-Wah Chung; Tak-Yeung Leung (Elsevier, 2017)
Objective: FloSeal© has been shown to be an alternative and effective method of hemostasis. The current study examines the various uses of FloSeal© in obstetric hemorrhage and gives an overview of the literature. Case reports: In this retrospective case review, a total of 11 cases with obstetric hemorrhage were reviewed throughout a period of one year. All but one case was successful in using FloSeal© in arresting the bleeding with hysterectomy avoided. FloSeal© can be considered when bleeding occurs locally at the placental bed, bladder base, adhesiolysis site, vaginal tears or at suture holes. Conclusion: FloSeal© was a quick and effective alternative for hemostasis and should be considered when conventional hemostatic techniques fails or is impractical.